Environmental Jurisprudence in India (Is People's Attitude Under Its Purview?). (December 2019) - Verma, Ravindra Kumar
It is environmental laws that regulate the environmental protection bodies and make them effective. With this view in mind, the article intends to examine the environmental jurisprudence in India in terms of evolution, pattern of delivery of environmental justice and place of people's attitude in the process. It was found that the superior judicial bodies including National Green Tribunal have set certain norms to deal with environmental cases against the polluters (mainly government bodies and private firms), but not for day-to-day activities of the people which pollute the environment sizeably. Besides, the article, on the basis of empirical studies, finds that despite having been aware of the menace of the environmental degradation and its gravity, people are less intended to be sensitive towards the problem owing to three-pronged reasons: First, they perceive environmental protection as the sole responsibility of state; second, sizeable of them have no spare time out of their livelihood engagements; and third, lack of leadership or community action at local level for the cause. The article prima facie finds that environmental jurisprudence in India has inadequately addressed the issue of people's say and environmentally hostile people's attitude towards environmental protection in the process.